CURRENT EVIDENCE OF PROTAMINE IN CAROTID SURGERY - Silva, Eduardo (2022)
Introduction and Objectives: Heparin administration is a standardized step in carotid surgery due to the reduced thromboembolic complication rate during perioperative period. This practice is not free of risks since hemorrhagic complications are associated with a larger number of reinterventions. Historically, protamine, as an agent capable of reverting the anticoagulant effects of heparin has raised controversy due to its association with carotid thrombosis and stroke. This article aims to review the published literature about the role of protamine reversal in carotid surgery. Methods: Using Pubmed, 10 articles published from January 2010 until the present date were selected, including two meta-analysis, one systematic review and six large-scale multicentric observational studies. The aim of this study was to identify the risk of myocardial infarction, stroke and death, as well as hemorrhagic complications after the administration of protamine. Results: Six of the selected articles focused on the effects of protamine during carotid endarterectomy, three on transfemoral carotid stenting and one on transcarotid stenting (TCAR). All the studies related to patients undergoing carotid endarterectomy where protamine had been administered, showed a statistically significant reduction in bleeding rate with a reduction in the number of patients undergoing surgical reintervention and the number of blood transfusions required. There was no statistical difference in the rate of myocardial infarction, stroke and death. The only study that analyzed the use of protamine on TCAR showed similar results to endarterectomy. Observational studies showed no differences in the incidence of stroke, myocardial infarction, death and bleeding complications with the use of protamine on transfemoral carotid stenting, yet a systematic review identified protamine as a risk factor for higher 30-day stroke rate. Patients submitted to surgical reinterventions showed higher rates of stroke, myocardial infarction and death, independently of the administration of protamine. Conclusion: The scientific data published on the last decade supports the safety of protamine reversal during carotid surgery, lowering hemorrhagic complications without showing an increase in thrombotic events. This is supported by meta-analysis and large-scale observational studies, going against the historical controversy surrounding protamine usage based on small sample analysis and local experience.